Hybrid treatment methods for diseases of thoracic aorta - О. А. jr. Mazur; I. O. Ditkivsky; B. V. Cherpak; V. I. Kravchenko (Ukrainian Journal of Cardiovascular Surgery, 2018)
Hybrid treatment of aortic pathology doesn’t have the drawbacks of conventional surgical methods. At the same time it has much wider possibilities of application than the endovascular method, which has significant anatomical limitations.In years 2014–2017 41 patients of Amosov National Institute of Cardiovascular Surgery with thoracic aortic pathology underwent hybrid treatment (open surgery on aortic arch branches and TEVAR). (n=19) patients had descending aortic aneurysm without dissection or rupture; (n=19) patients had aortic dissection (n=4 – acute, n=2 – subacute, n=13 – chronic), two patients had aortic aneurysm rupture and in one case the patient had PAU.Patients scheduled for elective surgery or those not in critical conditions had debranching of aortic arch at the first stage and TEVAR at the second stage. If they had life-threatening conditions (such as aortic rupture, visceral malperfusion), they underwent TEVAR immediately and after their condition improved, open surgery stage was conducted.Patient check-ups took place three and six months after hybrid treatment. Mortality rate was 2,4%, which is much lower than mortality rates for open surgical repair of descending aorta. Among the complications there were type I endoleak at a remote period; carotid-subclavian shunt thrombosis, left subclavian artery dissection and trauma of n. laryngeus recurrens (one case each). Three-month and six-month results of the treatment were good.